DINAMICS OF ARTERIAL STIFFNESS USING CAVI INDEX DEPENDS ON ADDED STATIN TO FIXED COMBINATION ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION. (June 2022) - Rekovets, Oksana; Sirenko, Yuriy; Torbas, Olena; Kushnir, Svitlana; Botsyuk, Yuriy; Primak, Galina
Abstract : Objective: Aim of this study was to evaluate dynamics of arterial stiffness using cardio-vascular index (CAVI), of the fixed triple combination of valsartan / amlodipine / hydrochlorothiazide and a double fixed combination of valsartan / amlodipine in the treatment of patients with arterial hypertension II-III degree depends on added statin therapy. Design and method: The study included patients with moderate and severe arterial hypertension without diabetes. Patients were divided into 2 groups. The first group (n = 59) was assigned a fixed combination of Val/Amlo/HCT of Val/Amlo plus statins. Patients in the second group (n = 40) received fixed combination Val/Amlo/HCT or Val/Amlo without statins. After 6 months of treatment there was control of therapy. Results: The study included 99 patients with moderate and severe hypertension. The average age of patients 1-st group - 58.05 ± 1.28 (37–75) years, 2-d group – 50, 05 ± 2.30 (24–76) years. Office SBP/DBP at the beginning 1-st group - 162.25 ± 1.53/97.36 ± 1.20 mm Hg and 160.85 ± 2.18/100.30 ± 1.64 mm Hg in 2-nd group. The office heart rate was 70.07 ± 1.14 bpm and 71.90 ± 1.71 bpm respectively. At baseline, 24-h ambulatory SBP/DBP baseline in 1-st group was – 141, 21 ± 1.10 /85, 63 ± 1.11 mm Hg and - 141, 80 ± 1.32 /86, 65 ± 1.33 mm Hg in 2-nd group. Decrease office blood pressure (SBP/DBP) in 1-st group was 35, 69/16, 52 mm Hg (p < 0, 05) and in 2-nd group – 35, 32/21, 77 mm Hg (p < 0, 05). There was increase the stiffness of the arterial wall in terms of cardio-vascular index CAVI in 2-d group without added statin. CAVI on the right/left site changed from 7.73 ± 0.26/7.62 ± 0.29 units to 8.63 ± 0.32/8.62 ± 0.32 units after treatment (p < 0, 05). Cardio-vascular index (CAVI) in 1-st group with added statin was not changed. CAVI on the right/left site changed from 8.32 ± 0.16/8.33 ± 0.19 units to 8.44 ± 0.16/8.24 ± 0.15 units after treatment (p > 0, 05). Conclusions: The added of statin to fixed combination antihypertensive therapy prevented the progression of arterial stiffness in patients with arterial hypertension.